2021
DOI: 10.3389/fpsyg.2021.637365
|View full text |Cite
|
Sign up to set email alerts
|

Economic Inequality Increases Status Anxiety Through Perceived Contextual Competitiveness

Abstract: Status anxiety, the constant concern about individuals’ position on the social ladder, negatively affects social cohesion, health, and wellbeing (e.g., chronic stress). Given previous findings showing that status anxiety is associated with economic inequality, we aimed in this research to test this association experimentally. A cross-sectional study (Study 1) was run in order to discard confounding effects of the relationship between perceived economic inequality (PEI) and status anxiety, and to explore the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 45 publications
2
46
1
4
Order By: Relevance
“…), whereas the idea that income inequality—a macroeconomic predictor—impacts cultural values and norms via school institutions seems to have more explanatory depth. Second, a reverse causality-based account is not consistent with extant experimental evidence documenting that induced income inequality increases competitiveness in the economic environment (e.g., Cheng et al, 2021; Melita et al, 2021; Sommet et al, 2019) and with Study 3, which documents similar effects in the academic environment.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…), whereas the idea that income inequality—a macroeconomic predictor—impacts cultural values and norms via school institutions seems to have more explanatory depth. Second, a reverse causality-based account is not consistent with extant experimental evidence documenting that induced income inequality increases competitiveness in the economic environment (e.g., Cheng et al, 2021; Melita et al, 2021; Sommet et al, 2019) and with Study 3, which documents similar effects in the academic environment.…”
Section: Discussioncontrasting
confidence: 72%
“…Observational (i.e., nonexperimental) evidence indicates that people residing in more unequal areas perceive their fellow residents as being more prone to competitiveness (Sommet et al, 2019), and that income inequality can disrupt the social fabric and break the norms of reciprocity that facilitate cooperation (Kawachi & Kennedy, 1999; but see Kim et al, 2021). Experimental evidence confirms this twofold tendency: When participants are asked to imagine living in a society with high rather than low levels of income inequality, they picture their fellow inhabitants as being more likely to care about personal success, social recognition, and competitiveness, rather than the welfare of others, social justice, and cooperativeness (Cheng et al, 2021;Melita et al, 2021;Sánchez-Rodríguez et al, 2020;Sánchez-Rodríguez et al, 2019).…”
Section: Income Inequality Competitiveness and Cooperativeness In The...mentioning
confidence: 92%
“…We asked participants to report the frequency of perceived economic inequality in their everyday life by answering the following question (from 1 = never, to 5 = very frequently): "How often do you see situations of economic inequality in your daily life?" PEIEL's measures in recent studies have shown satisfactory validity evidences (see Melita et al, 2021;Sánchez-Rodríguez et al, 2020).…”
Section: Perceived Economic Inequality In Everyday Life (Pelel)mentioning
confidence: 99%
“…In this way, comparing the reference group members' increased wealth with one' own can trigger status anxiety (Ferrer-i-Carbonell and Ramos, 2012;Charles and Lundy, 2013). Therefore, living in high economic inequality conditions can increase concerns about the social position, and in turn perpetuate status anxiety (Walasek and Brown, 2019;Melita et al, 2021). Importantly, from our point of view, status anxiety should not just be considered as a consequence of economic inequality, but it could also trigger, in turn, other important psychological processes, such as consumption decisions, aimed to look for status seeking.…”
Section: Seeking For Social Statusmentioning
confidence: 99%